182k views
0 votes
-8(8v + 1) - 2 = -394

User Plantage
by
5.2k points

2 Answers

4 votes
The answer to your
Question v=6
User Fatiu
by
6.1k points
4 votes

Answer:

v = 6

Explanation:

Solve for v:

-8 (8 v + 1) - 2 = -394

-8 (8 v + 1) = -64 v - 8:

-64 v - 8 - 2 = -394

Grouping like terms, -64 v - 8 - 2 = -64 v + (-8 - 2):

-64 v + (-8 - 2) = -394

-8 - 2 = -10:

-10 - 64 v = -394

Add 10 to both sides:

(10 - 10) - 64 v = 10 - 394

10 - 10 = 0:

-64 v = 10 - 394

10 - 394 = -384:

-64 v = -384

Divide both sides of -64 v = -384 by -64:

(-64 v)/(-64) = (-384)/(-64)

(-64)/(-64) = 1:

v = (-384)/(-64)

The gcd of -384 and -64 is -64, so (-384)/(-64) = (-64×6)/(-64×1) = (-64)/(-64)×6 = 6:

Answer: v = 6

User Silvio Donnini
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.